The roles of long noncoding RNAs in breast cancer metastasis - Liu, Lingxia; Zhang, Yu; Lu, Jun (Cell death & disease, 2020)
Breast cancer is the most significant threat to female health. Breast cancer metastasis is the major cause of mortality in breast cancer patients. To fully unravel the molecular mechanisms that underlie the breast cancer cell metastasis is critical for developing strategies to improve survival and prognosis in breast cancer patients. Recent studies have revealed that the long noncoding RNAs (lncRNAs) are involved in breast cancer metastasis through a variety of molecule mechanisms, though the precise functional details of these lncRNAs are yet to be clarified. In the present review, we focus on the functions of lncRNAs in breast cancer invasion and metastasis, with particular emphasis on the functional properties, the regulatory factors, the therapeutic promise, as well as the future challenges in studying these lncRNA.